Placement preparation : more than 1000 questions - Parthasarathy, S. (New Age International, 2006)
This book is meant for students who are trying to find the best means of successfully passing through the highly technical selection process in the Information Technology Industry. The industry is thriving now and its usual recruitment procedure is to some extent difficult though somewhat standardized.